From Ritual to Ruin: Satish Alekar’s Deluge and the Postmodern Indian Consciousness - Nikam, Sudhir V.; Shelke, Balaji B. (International Journal of Psychosocial Rehabilitation, 2019)
Satish Alekar’s Deluge (originally Mahapoor, later adapted and translated) embodies the collapse of ritualistic and moral certainties in post-Independent India. Through its dark humor, fragmented narrative, and metaphoric critique of urban decay, Deluge transforms the traditional Marathi stage into a site of existential questioning. This paper explores Alekar’s dramaturgy through the lens of postmodern consciousness—marked by irony, simulacra, disillusionment, and fragmented identities. Drawing on theorists such as Jean Baudrillard, Fredric Jameson, and Linda Hutcheon, the analysis examines how Alekar’s play exposes the moral and spiritual erosion beneath modern India’s surface of progress. The paper argues that Deluge functions not merely as a social satire but as a postmodern meditation on death, faith, and the exhaustion of meaning in contemporary life.